2023
DOI: 10.1038/s41467-023-40236-7
|View full text |Cite
|
Sign up to set email alerts
|

Observation of geometry-dependent skin effect in non-Hermitian phononic crystals with exceptional points

Abstract: Exceptional points and skin effect, as the two distinct hallmark features unique to the non-Hermitian physics, have each attracted enormous interests. Recent theoretical works reveal that the topologically nontrivial exceptional points can guarantee the non-Hermitian skin effect, which is geometry-dependent, relating these two unique phenomena. However, such novel relation remains to be confirmed by experiments. Here, we realize a non-Hermitian phononic crystal with exceptional points, which exhibits the geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, with the recent development of non-Hermitian physics, it has been found that not only the edge modes but all the bulk states can pile up at the edges of the systems as well, and such phenomenon is dubbed as noptn-Hermitian skin effects [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In these cases, the bulk boundary modes can be extremely sensitive to local perturbations and the conventional BBC can be broken [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the recent development of non-Hermitian physics, it has been found that not only the edge modes but all the bulk states can pile up at the edges of the systems as well, and such phenomenon is dubbed as noptn-Hermitian skin effects [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In these cases, the bulk boundary modes can be extremely sensitive to local perturbations and the conventional BBC can be broken [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Manifesting as a boundary localization of eigenstates, NHSE becomes more sophisticated in higher dimensional systems, where richer structures of boundaries emerge from different geometries [51][52][53][54][55][56][57] and defects [58][59][60][61][62] of lattices. In this topical review, we provide an overview of the discovery and developments of HSTE [63], a novel phenomenon arising from the interplay of NHSE and topological boundary states in two-or higher-dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, even for a given E 0 , we are left with two complex variables and one complex constraint equation, whose solution is a 2D Riemann surface in the 4D space defined in (Re k x , Im k x , Re k y , Im k y ), making it challenging to handle both analytically and numerically. Secondly, the shape of OBC geometry can significantly affect the NHSE in two and higher dimensions [59,[64][65][66][67][68][69][70][71]. For instance, in the geometry-dependent skin effect [59], the NHSE disappears in square geometry but emerges in triangle geometry.…”
mentioning
confidence: 99%